An Analysis of Reproductive Health Risks, Health Worker Role, and Family Prosperity as a Determinant of Stunting Prevention - Fikitri Marya Sari; Yusran Fauzi; Wulandari Wulandari (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2026)
Background: Stunting is a complex public health issue, influenced by various biological aspects, medical services, and socioeconomic conditions. In Lebong Regency, the prevalence of stunting showed variability, with a recent increase that requires a thorough investigation of its determinants. Reproductive risks in couples of childbearing age (PUS) related to the 4T criteria (too young, too old, too close pregnancy interval, and too many children), the role of health workers, and family prosperity are thought to correlate with stunting prevention.Method: This study employed a quantitative analytical design with a cross-sectional approach, utilizing secondary data from the National Population and Family Planning Board (BKKBN) in 2024. A total of 20,327 families in Lebong Regency became the study population. Following validation and data cleaning stages, 17,922 families were selected as samples using purposive sampling based on the criteria of adequate data completeness. The analyzed variables included reproductive risks of PUS 4T, the role of health workers, family prosperity, and stunting prevention Data analysis included univariate analysis, bivariate analysis using the chi-square test, and multivariate analysis through multiple logistic regression to determine the most influential factors.Result: The investigation revealed that factors including reproductive risk of PUS 4T, health workers’ involvement, and family prosperity conditions significantly correlated with stunting prevention efforts (p<0.001). Multivariate analysis identified reproductive risk of PUS 4T as the most dominant predictive indicator (OR=2.109; 95% CI: 1.958–2.273). Therefore, this study emphasized the need to strengthen reproductive health programs, increase the effectiveness of the role of health workers, and improve family prosperity through an integrated approach.Keywords: Reproductive risk, Health worker, Prosperity, Stunting